Penerapan Metode System Usability Scale dalam Pengujian Rancangan Sistem Rekomendasi Tempat Penyewaan Kendaraan Bermotor - Sani, Richa Mutiara; Mogi, I Komang Ari (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Website-based technology information systems have been widely used. One of them is the recommendation system. Along with the development of technology, people easily use and access anything on the Internet. This recommendation system was created as a form of User Interface and User experience for system Users. The User Interface is used to meet User needs while the User experience is used as an assessment of the success of the system that has been designed. To determine the usability of the system using the System Usability Scale (SUS) method. In designing this system, it is hoped that it can help the recommendation system for motorized vehicle rentals.